Can muscle synergies shed light on the mechanisms underlying motor gains in response to robot-assisted gait training in children with cerebral palsy? - Gloria P. Vergara-Diaz; Stefano Sapienza; Jean-François Daneault; Eric Fabara; Catherine Adans-Dester; Giacomo Severini; Vincent C. K. Cheung; Carmen Echevarría Ruiz de Vargas; Donna Nimec; Paolo Bonato (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Children with cerebral palsy (CP) often experience gait impairments. Robot-assisted gait training (RGT) has been shown to have beneficial effects in this patient population. However, clinical outcomes of RGT vary substantially from patient to patient. This study explored the hypothesis that clinical outcomes are associated with changes in muscle synergies in response to RGT. Methods Thirteen children with CP and Gross Motor Function Classification Scale (GMFCS) levels I–IV were recruited in the study. Children participated in a 6 week-RGT intervention and underwent clinical evaluations and gait studies—with focus on the analysis of electromyographic (EMG) data—pre- and post-training. Lower-limb muscle synergies were derived from the EMG recordings. Pre- vs. post-RGT clinical outcomes and muscle synergies were compared to explore potential relationships. Results Three and, less often, two muscle synergies were detected in study participants pre-RGT. Linear mixed effect models showed that composition of the muscle synergies and their temporal activation coefficients present deviations from normative data proportional to the severity of functional limitations (i.e., GMFCS levels, p < 0.01). At a group level, changes in muscle synergies pre- vs. post-RGT did not significantly correlate with changes in clinical outcomes (p > 0.05). However, it was observed that participants who displayed prominent changes in muscle synergies also displayed large improvements in clinical scores. Conclusions Gait impairments in children with CP were associated with muscle synergies that deviated from normative. Participants who demonstrated the most substantial improvements in clinical scores following RGT exhibited multiple changes in the muscle synergies. However, no statistically significant correlations were identified at the group level. Future studies relying on larger datasets are needed to further investigate this observation and potential underlying mechanisms.